Tourism Potential of Mandalika Destination - Suma Thesa; Ni Made Ari Oka Megawathi; Sahril Wahyudi; Anak Agung Made Dwi putri Kusumayanti; Ni Komang Ayu Wandira; Sirin Huwaida; Wahyuni; Ketut Surata; Putu Utama (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the tourism management and economic potential of the Special Economic Zone (SEZ) Mandalika. This case study identifies challenges such as high ticket prices, limited accessibility, and inadequate information, which hinder local participation. Using a qualitative approach, data was collected through interviews, observations, and document analysis. The findings highlight the need for more inclusive and affordable promotional strategies, and strengthening community relations. Recommendations include providing more accessible entry options and more relevant promotions to enhance local engagement and support economic growth and cultural preservation in Mandalika.